Gender Justice in Saudi Arabia: Sociotechnical Institutions' Approach to Addressing Domestic Violence Against Women and Men - Noor, Layla Abdullah (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2024)
The aim of this research is to determine the effectiveness of a sociotechnical institutional approach in overcoming domestic violence against women and men in Saudi Arabia with a focus on achieving gender justice. This research uses an extensive literature review method by examining scientific literature, official documents, and reports from various sources to gain an in-depth understanding of this problem. This analysis involves a synthesis of literature findings to understand the dynamics of domestic violence and the effectiveness of sociotechnical strategies in promoting gender justice in Saudi Arabia. The research results show that domestic violence is a global phenomenon that is understood and handled with different approaches from Islamic, Feminist and Western perspectives. The Islamic perspective emphasizes the values of justice, respect and reconciliation in marital relations, as well as fighting for women's rights and opposing violence within the framework of religious teachings. Feminist approaches, particularly in Western contexts, highlight gender-based power dynamics and urge to address inequality as a root cause of domestic violence. In addition, the family violence perspective and ecological violence theory offer a broader view of this issue. In Saudi Arabia, the role of sociotechnical institutions is very important in overcoming the problem of domestic violence. A multidisciplinary approach that includes technology, legal reform, education, and community support contributes to creating a safer and more supportive environment for women. This research concludes that a sociotechnical institutional approach can be an effective strategy in achieving gender justice and reducing domestic violence in Saudi Arabia.